Hepatitis C in Puerto Rico: a time for public health action - Pérez, Cynthia M.; Albizu, Carmen; Peña, Marisol; Torres, Esther A.; Reyes, Juan C.; Colón, Héctor; Ortiz, Ana P.; Suárez, Erick (Puerto Rico Health Sciences Journal, 2007)
Studies investigating the seroprevalence of HCV infection have been carried out in diverse populations, showing an estimated worldwide prevalence of 3%. A seroprevalence survey conducted among randomly selected non-institutionalized adults aged 21-64 years in San Juan, Puerto Rico in 2001-2002 revealed that 6.3% were positive for HCV antibodies. These data suggest that Puerto Ricans are burdened with a significantly greater prevalence of HCV infection compared to the general United States population aged 20-69 years (0.9%-4.3%). This article illustrates data from different sources that taken together establish the need to start addressing HCV infection in Puerto Rico with prompt and decisive public health actions. Some of these include (1) establish hepatitis C prevention as a priority for state and municipal public health authorities, (2) raise awareness and educate target populations about HCV transmission and prevention, (3) increase clinician awareness of the HCV reporting system and the epidemiology and management of hepatitis C, (4) increase availability of diagnosis and treatment facilities, (5) increase access to effective drug treatment services, and (6) develop appropriate control measures to help reduce continued transmission in correctional settings.